Labour force transitions - Rui Castro; Fabian Lange; Markus Poschke (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
Labor Force States and flows between are useful tools to model individual dynamics in the labor market. This chapter reviews recent literature uncovering substantial heterogeneity in transitions across Labor Force States. We review methods and results by replicating leading studies using Canadian data and relate our findings to important literatures on recall non-employment, duration dependence, and job ladders.
Keywords: 330